Time for a change? - Ashley Garlick (University of West London, 2020)
Organisations are constantly having to make difficult decisions over where to direct finite company resources. These decisions need to be driven by a clear strategy and companies need to be prepared to manage any resulting change. This article explores the decision by the British Red Cross to withdraw from the growing event medical sector.